The Fun Food Barbeque as a Product Innovation of the Food and Beverage Department, the Neo+ Awana Hotel, Yogyakarta - Carlos Iban; Arismagita Arismagita (Jurnal Pariwisata Terapan, 2017)
The growth of the hotel business in Yogyakarta is currently increasing up. Based on data from the Association of Indonesian Hotels and Restaurants, the total of new hotels to be built in Yogyakarta reaches 110 hotels. With reference to these growth figures, hospitality management is currently not only focused on providing accommodation, but also going further to selling other hotel products, such as food and beverages. This research took a case study about the product innovation of Neo + Awana Hotel Yogyakarta, with a developing event called "Fun Food Barbeque". The method used is descriptive qualitative with primary data collection using participant observation and interviews. The results shows that the first implementation of the Barbeque Fun Food event is not optimal, because guests are not interested in western food and also the menu has many things to offer. With the changing innovation of barbecue products into fusion food with a menu that is a blend of Indonesian food with western food, the Fun Food Barbeque event becomes more interesting.